Glucocorticoid and progestin receptors are differently involved in the cooperation with a structural element of the mouse mammary tumor virus promoter. - Le Ricousse, S (1996)
We have previously characterized a regulatory element located between -294 and -200 within the mouse mammary tumor virus (MMTV) long terminal repeat (LTR). This element termed AA element cooperates with the glucocorticoid response elements (GREs) for glucocorticoid activation. Here we show that in a MMTV LTR wild type context, the deletion of this element significantly reduces both glucocorticoid and progestin activation of the promoter. Deletion of the two most distal GREs forces the glucocorticoid receptor (GR) and the progestin receptor (PR) to bind the same response elements and results in a dramatic decrease in the inducibility of the MMTV promoter by the two hormones. The simultaneous deletion of the two distal GREs and of the AA element abolishes completely the glucocorticoid-induced activation of the promoter. In contrast it restores a significant level of progestin-induced activation. This different effect of the double deletion on glucocorticoid- and progestin-induced MMTV promoter activation is not cell specific because it is also observed, and is even stronger, when either GR or PR is expressed in the same cell line (NIH 3T3). This is the first description of a mutated MMTV promoter that, although retaining GREs, is activated by progestins and not by glucocorticoids. This suggests a different functional cooperation between protein(s) interacting with the AA element and GR or PR. Cotransfections with constructs containing wild-type or mutated MMTV LTR with either PR lacking its C-terminal domain or GR/PR chimeras in which the N-terminal domains have been exchanged demonstrate that the N-terminal domains of the receptors specify the different behavior of GR and PR regarding the AA element.